Immune checkpoint inhibitors in non-conventional histologies of renal-cell carcinoma - Melissa Bersanelli; Sara Elena Rebuzzi; Giandomenico Roviello; Martina Catalano; Matteo Brunelli; Mimma Rizzo (Taylor & Francis Group, 2023)
For years, prospective randomized clinical trials excluded patients with non-conventional histologies of renal cell carcinoma (RCC). The paucity of data has led to adopting the same treatment strategies used for clear-cell RCC (ccRCC). In the present narrative review, we explored state of the art about use of immune checkpoint inhibitors (ICIs) in variant histologies of RCC. According to the results collected, ICIs as monotherapy showed promising antitumor activity in advanced non-clear cell (ncc)RCC. The objective response rate (ORR) was similar to that observed with single-agent anti-PD-1 in the ccRCC population, either in the first-line or the second-line setting, and responder patients experienced an early and durable benefit. Combined ICI-based strategies have shown increasing evidence in nccRCC and robust results in the sarcomatoid variants of RCC. A definitive recommendation about treating non-conventional histologies, either in adjuvant or metastatic settings, should be supported by more extensive dedicated trials.